Coeficiente de escoamento de enchente em duas bacias hidrográficas experimentais em Uberlândia - MG - Oliveira, Letícia Martins de (2018)
With the notorious increase in the use of water resources, the understanding of the dynamics of a watershed turns out to be very important. The direct runoff, one of the phases of the cycle, is one of the most fundamental concepts in hydrology. The runoff coefficient represents the amount of runoff that a given river basin is capable of generating during rainy events and also summarizes all the factors that affect the generated flow. When focusing on relatively small watersheds, the knowledge and the quali-quantitative data on water resources are still incipient. In this context, the present work aimed directly measure the runoff coefficient (C) of two experimental river watersheds located in the Cerrado of Minas Gerais, and to estimate by three different methodologies: rational method, SCS Runoff Curve Number Method and by means of values contained in tables of the technical literature. Values of C calculated by using the observed effective precipitation presented variation for the Experimental Watershed of Glória Creek (EWGL) which went from 0.004 to 0.074, while for the Experimental Watershed of Água Vermelha Creek (EWAV), the variation was between 0.0003 and 0.014. Unlike the previous method, the values of effective precipitation estimated by the CN-SCS method varied between 0000001 and 0,328 for the EWGL and between 0.0001 and 0.35 for the EWAV. When calculations were performed with the Rational method, C alternated between 0.017 to 0.262 in EWGL, while in EWAV it ranged from 0.01 to 0.16. On the other hand, when the coefficient C was estimated from tables often found in the technical literature, it varied from 0.325 to 1 (mean value of 0.34) for the EWGL and for the EWAV, it went from 0.29 to 1 (with mean of 0.42). On both experimental watersheds, none of the values of C obtained by the different methods came close to matching when compared with each other. The largest difference, both in EWGL and EWAV, was observed between the mean value of C directly measure and C from the technical literature. The Rational method was more adequate for the estimation of C. This variation is a result of the variability of the values of C found in this work, which in turn, reflects the complexity related to this parameter.